2016
DOI: 10.1111/njb.00991
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the genus Tordylium (Tordylineae, Apioideae, Apiaceae) inferred from morphological data

Abstract: Tordylium is a medium‐sized genus characterized by an annual habit, 1–3‐pinnate leaves, dorsally compressed mericarps, and thickened mericarp margins. Eighteen Tordylium species occur in Turkey, of which seven are endemic. Although the morphology of the genus is well known, evolutionary relationships among its species have never been evaluated. In this study, phylogenetic relationships within Tordylium are investigated using parsimony analysis based on morphological data from 17 ingroup and 15 outgroup taxa fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To understand the evolution of chromosome numbers the phylogenetic hypothesis of Doğru-Koca [25] has been used (Figure 2). Tordylium has too heterogeneous cytotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the evolution of chromosome numbers the phylogenetic hypothesis of Doğru-Koca [25] has been used (Figure 2). Tordylium has too heterogeneous cytotypes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the last revision [16], the infrageneric classification has been formed such as Ainsworthia as subgenus; Condylocarpus and Hasselquistia as sections. However, the phylogenetic topology based morphological data contradicts Al-Eisawi and Jury's [16] infrageneric classification of the genus [25]. Therefore, it is revealed that the current subgeneric and sectional divisions are unnatural.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation